A Low Advanced Lung Cancer Inflammation Index Predicts a Poor Prognosis in Patients With Metastatic Non–Small Cell Lung Cancer - Lu, Ping; Ma, Yifei; Kai, Jindan; Wang, Jun; Yin, Zhucheng; Xu, Hongli; Li, Xinying; Liang, Xin; Wei, Shaozhong; Liang, Xinjun (Frontiers in Molecular Biosciences, 2022)
Introduction: Inflammation plays a crucial role in cancers, and the advanced lung cancer inflammation index (ALI) is considered to be a potential factor reflecting systemic inflammation. Objectives: This work aimed to explore the prognostic value of the ALI in metastatic non-small-cell lung cancer (NSCLC) and classify patients according to risk and prognosis. Methods: We screened 318 patients who were diagnosed with stage IV NSCLC in Hubei Cancer Hospital from July 2012 to December 2013. The formula of ALI is body mass index (BMI, kg/m2) × serum albumin (Alb, g/dl)/neutrophil-lymphocyte ratio (NLR). Categorical variables were analysed by the chi-square test or Fisher’s exact test. The overall survival (OS) rates were analysed by the Kaplan–Meier method and plotted with the R language. A multivariate Cox proportional hazard model was used to analyse the relationship between ALI and OS. Results: According to the optimal cut-off value determined by X-tile software, patients were divided into two groups (the ALI < 32.6 and ALI ≥ 32.6 groups), and the median OS times were 19.23 and 39.97 months, respectively (P < 0.01). A multivariable Cox regression model confirmed that ALI and chemotherapy were independent prognostic factors for OS in patients with NSCLC. OS in the high ALI group was better than that in the low ALI group (HR: 1.39; 95% CI: 1.03-1.89; P = 0.03). Conclusions: Patients with a low ALI tend to have lower OS among those with metastatic NSCLC, and the ALI can serve as an effective prognostic factor for NSCLC patients.